2014
DOI: 10.1108/ijefm-07-2013-0019
|View full text |Cite
|
Sign up to set email alerts
|

Mega-event volunteers, similar or different? Vancouver 2010 vs London 2012

Abstract: Purpose – The purpose of this paper is to compare motivations of volunteers at two mega multi-sport events. Design/methodology/approach – The research used a quantitative research design to survey volunteers at the Vancouver 2010 Olympic and Paralympic Winter Games (n=2,066) and the London 2012 Olympic and Paralympic Games (n=11,451) via an online questionnaire based upon the Special Event Volunteer Motivation Scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 37 publications
2
51
0
Order By: Relevance
“…This raised the public's expectations of potential Games legacies related to volunteerism [36]. For example, it was suggested that 40% of applicants for London 2012 volunteer roles were inspired to volunteer for the first time, even though a survey of London 2012 Games Makers found later that only 20% of respondents were volunteering for the first time [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This raised the public's expectations of potential Games legacies related to volunteerism [36]. For example, it was suggested that 40% of applicants for London 2012 volunteer roles were inspired to volunteer for the first time, even though a survey of London 2012 Games Makers found later that only 20% of respondents were volunteering for the first time [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example; volunteers with either set of values might resent LOCOG taking advantage of their market position or feel they had not been treated with sufficient respect so codes recording this were not used. Similarly the motive of being part of a once in a lifetime-event ('being part of it'), has been shown to dominate in volunteering for the Olympic Games (Dickson, et al 2014) but across all age groups. Codes are described in Table 1.…”
Section: Coding and Analysismentioning
confidence: 99%
“…Similar to other studies of tourism volunteering, research on mega-event volunteers is focused on the motivation of mega-event volunteers (e.g. Dickson, Benson & Terwiel, 2014;. V O G -in-atheir motivations and expectations are extremely high, as noted at the 2000 Sydney Olympics (Green & Chalip, 2004), the 2002 Commonwealth Games , and the Vancouver Winter Olympic Games (Dickson, Benson & Terweil, 2014).…”
Section: Volunteers At Mega-eventsmentioning
confidence: 99%
“…However, a second motivational cluster, identified by both Dickson et al and Alexander et al (2015) analysis, included motivational statements L United Kingdom, and being proud of London and the United Kingdom. In the Dickson et al (2014) analysis this was the second strongest cluster of motivations, measured by the mean score of responses.…”
Section: Volunteers At Mega-eventsmentioning
confidence: 99%